A Bibliometric Study of Indian Journal of Pure and Applied Mathematics - Narang, Asha; Kumar, Anil (Journal of Information and Knowledge, 2014)
Bibliometric analysis of 4798 citations appended to 400 articles in five volumes-34(2003) to 38(2007) and maiden volume (1970) of the Indian Journal of Pure and Applied Mathematics has been carried out to observe the number of contributions and their distribution in different volumes, authorship pattern, foreign and Indian author contributions, citation analysis and number of pages used in each volume. A comparative study of articles published in 5 volumes vis-à-vis those in volume 1 has been made. Results indicate a decrease in the number of contributions in successive volumes. The most cited documents are articles from research journals. The number of foreign contributors is more than Indian contributors. Growth and popularity of the journal is showing mixed trends i.e. upward and downward progress.